Application of an automated identification and quantification system with a GC/MS database (AIQS-DB) for simultaneousanalysis of phthalate esters and sterols in air particles - Dung, Truong Anh; Trinh, Ha Thu; Dung, Nguyen Tran; Duong, Hanh Thi (Vietnam Journal of Science and Technology, 2019)
The aim of this study is to apply an automated identification and quantification system with a GC-MS database (AIQS-DB) for simultaneous analysis of phthalate esters (PAEs) and sterols in air particles. Air particles samples were collected on the roof of building located by the side of a busy street with heavy traffic load (Pham Van Dong street) (AP1) and in a highly populated residential area (Phu Do town) (AP2). At each sampling location, day and night samples were collected separately (around 10 h for each sample) continuously 6 d using a Kimoto high-volume air sampler. Air particle samples were then extracted by dichloromethane and determined and quantified by GC/MS instrument with the AIQS-DB. Analytical results of 12 PAEs and 13 sterols in air particles samples showed that five out of 12 PAEs and seven out of 13 sterols were detected. Di(2-ethylhexyl)phthalate (DEHP), di-n-butyl phthalate (DBP) and di-iso-butyl phthalate (DiBP) concentrations were highest, contributed 94% of the total detected phthalates concentration. Cholesterol and beta-sitosterol were detected in all the samples and accounted more than 70% of the total detected sterols concentration at Phu Do town. This is the first study on the application of AIQS-GC for simultaneous determination of PAE and sterols in the air particle, especially results obtained from this study provides new important information about the level and occurrence of sterol in air in Vietnam.